Positive solutions for a system of fractional differential equations with p-Laplacian operator and multi-point boundary conditions - Luca, Rodica (Nonlinear Analysis: Modelling and Control, 2018)
We investigate the existence and nonexistence of positive solutions for a system of nonlinear Riemann–Liouville fractional differential equations with parameters and p-Laplacian operator subject to multi-point boundary conditions, which contain fractional derivatives. The proof of our main existence results is based on the Guo–Krasnosel’skii fixed-point theorem.